Influência da temperatura sobre plantas aquáticas em pós-tratamento de efluente da suinocultura - Weirich, Carlos Eduardo (2009)
This study aimed to evaluate the influence of temperature on production of biomass and retention of nitrogen and phosphorus in a treatment system for swine effluent, composed of two species of aquatic plants Eichhornia crassipes (water hyacinth) and Pistia stratiotes (lettuce water). The work was accomplished at the Universidade Estadual do Oeste do Paraná- Paraná State, Campus of Toledo - PR, in the periods that were on 19 February to 19 March 2008 and August 11 to 09 September 2008, referring to the summer and winter, respectively. The system was composed by 24 experimental tanks built in concrete with a length of 1,5 m, width of 0,25 m and depth of 0,16 m. A completely randomized design was used two species of macrophytes, water lettuce and water hyacinth and two periods with four replications. Water samples were collected at entry and exit system at the beginning and end of the experiment evaluating the total nitrogen (TN), total phosphorus (TP), pH, electric conductivity and dissolved oxygen. The water temperature together with the maximum and minimum temperature and air humidity were measured daily. Biomass production was analysed in the end of the experiment. The proximate analysis of biomass plants examined in the dry, were different (P <0,05) for the periods, the ash content grow in the shoot (CZPA) and root (CZR), phosphorus in the shoot (PPA ) and nitrogen in the root (NR) and shoot (NPA). As for the treatments showed meaning difference (P <0,05) for the crude protein in shoot (PBPA), gray in the root (CZR) and shoot (CZPA). The most remotion of water, as for the water hyacinth as for the track, was observed in summer with values of 85,71% and 88,69%, respectively. These values did not differ statistically from those observed for the winter. For PT a higher removal was observed on treatment with water hyacinth in the winter (43,37%) and on the runway during the summer (43,33%). The production of biomass of water hyacinth was 4,04 and 3,19 kg m-2 during the summer and winter, respectively, while the runway was 1,78 and 0,71 kg.m-2 for the same periods. The results obtained in this experiment, conclude that the plants had high biomass production and a high potential for accumulation of nitrogen and phosphorus in their plant tissue. The temperature of air and water showed variation during the periods of the experiment, indicating the summer period that favored the best performance of species evaluated